Review Keragaman dan Metode Pengolahan Umbi-Umbian Lokal Nusa Tenggara Timur - Hyldegardis Naisali; Panggulu Ahmad Ramadhani Utoro; Jatmiko Eko Witoyo (Universitas Muhammadiyah Semarang, 2023)
East Nusa Tenggara (ENT) is one of Indonesia's regions with a dry climate with low annual rainfall and a diversity of local tuber flora biodiversity, which has been communicated in various scientific publications. However, information on the diversity and utilization of local tubers is still partial in certain areas in ENT. This article aims to briefly review the diversity and use of local ENT tubers by local communities. The method used in preparing this article is the study of literature from various scientific journals and books related to local tubers. Several studies reported that Manihot esculenta and Ipomoea batatas are local tubers widely cultivated in almost all areas of ENT. Colocasia esculenta, Solanum tuberosum, Canna edulis, Dioscorea esculenta, Dioscorea bulbifera, and Amorphophallus muelleri Blume are local tubers which have begun to be cultivated in a limited manner in several areas in ENT. Apart from that, many wild minor tubers are found around yards and forests in almost all areas of ENT, such as Dioscorea alata, Amorphophallus paeoniifolius, and Dioscorea hispida. Local tubers, both cultivated and growing wild in ENT, function as an alternative source of carbohydrates during the lean season. The method of processing local tubers by the oENT's people into food is still straightforward and traditional: boiling, burning, and frying or processing them into tuber flour.